The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/healthcare9030355
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity Virtual Objective Structured Clinical Examinations with Standardized Patients in Nursing Students: An Innovative Proposal during the COVID-19 Pandemic

Abstract: In response to the cancellation of in-person objective structured clinical examinations (OSCEs) prompted by confinement due to the COVID-19 pandemic, we designed a solution to adapt our traditional OSCEs to this new reality in nursing education. We implemented an innovative teaching proposal based on high-fidelity virtual OSCEs with standardized patients. The purposes of our study were to describe this innovative teaching proposal and compare nursing competence acquisition in final year nursing students throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Three descriptive studies (see Table 6) conducted in Spain, 36 Japan 37 and USA 38 provided evidence for the effectiveness of alternative educational delivery strategies for nursing students studying a specific module in human genomics, 37 simulation in paediatric clinical practice 38 and for the delivery of remote OSCEs with COPD patients 36 during the COVID-19 pandemic. All three studies compared a group of students receiving a remotely delivered educational package with a group receiving standard, in-person education.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three descriptive studies (see Table 6) conducted in Spain, 36 Japan 37 and USA 38 provided evidence for the effectiveness of alternative educational delivery strategies for nursing students studying a specific module in human genomics, 37 simulation in paediatric clinical practice 38 and for the delivery of remote OSCEs with COPD patients 36 during the COVID-19 pandemic. All three studies compared a group of students receiving a remotely delivered educational package with a group receiving standard, in-person education.…”
Section: Resultsmentioning
confidence: 99%
“…Weston and Zauche 38 substituted virtual simulation using the i-Human platform to replace in-person clinical practice and simulation laboratory learning. Outcomes explored were competency (n=2) 36,37 confidence (n=1), 37 and knowledge (n=2). 37,38…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies running similar virtual OSCEs have shown that it is cost-efficient, useful and feasible in the current global situation with a potential role even in the post-pandemic phase [ 15 ]. As our OSCE workshops were all online, we were able to reach students on an international level, thus providing students from across the world with the opportunity to participate and access resources that they may have otherwise been unable to reach if the sessions were run in-person.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies running similar virtual OSCEs have shown that it is cost-e cient, useful and feasible in the current global situation with a potential role even in the post-pandemic phase [15]. As our OSCE workshops were all online, we were able to reach students on an international level, thus providing students from across the world with the opportunity to participate and access resources that they may have otherwise been unable to reach if the sessions were run in-person.…”
Section: Discussionmentioning
confidence: 99%